SIMBOL-SIMBOL DALAM IKLAN NIKE DI MEDIA YOUTUBE (ANALISIS SEMIOTIKA) - Zigit Dwi Dandi Pou; Jultje Aneke Juneke Rattu; Muh. Hasan Basri (An Nafi': Multidisciplinary Science, 2026)
Nike symbolizes the Greek goddess of strength, speed, and victory, which is often reflected in the brand's visual narratives. This research, titled "Symbols in Nike Advertisements on YouTube Media (A Semiotic Analysis)," aims to analyze how symbols are represented and interpreted in Nike’s “What If You Can” advertisement through the lens of Roland Barthes’ semiotic theory. Using a qualitative approach and virtual ethnographic method, this study examines 10 selected advertisement scenes published on YouTube. The analysis identifies 10 denotative meanings—such as a student sitting alone on school stairs—and 10 connotative meanings—such as emotional struggle and the pursuit of dreams. Additionally, the study reveals 10 myths that reflect broader ideological constructs, including perseverance, empowerment, and modern youth identity. These findings underscore how advertising, as a cultural text, constructs layered meanings through visual symbols and contribute to shaping audience perceptions. This research highlights the significance of semiotics in understanding media messages and recommends further studies involving various platforms and audience demographics.